Simulation study on forward osmosis desalination process - Syaza Syafiqah, Muhamad Kamel (2015)
The current scenario of Malaysia water crisis demands innovative and novel technologies that not only provide elevated throughput and productivity, but also ensures optimum energy efficiency at the same time. Launching a RM 60Million new water desalination plant is Sarawak (Choice, 2013) reflects the necessity of seawater desalination in Malaysia. Today, the most consistent and reliable technology to extract fresh water from seawater is the reverse osmosis (RO) process. However, the energy is consumed by this process, including the pressure exchangers at the brine stream. Furthermore, it also faces the issue of membrane fouling. In the turn of the new century, scientists have shown keen interest in forward osmosis (FO) process in order to address the challenges faced by the RO process. FO is an osmotically driven membrane process that takes advantage of the osmotic pressure gradient to drive water across the semipermeable membrane from the feed solution (low osmotic pressure) side to the draw solution (high osmotic pressure) side. FO delivers many potential advantages such as less energy input, lower fouling tendency, and higher water recovery than others technologies. Objective of this study is to perform FO desalination of seawater simulation for the whole process in Aspen Plus and to study the optimum parameter for FO membrane desalination process which is ammonia bicarbonate and also to estimate the electrical equivalent of energy required and compare it with other desalination processes. Methodology in simulating FO desalination process is going to be develops using Aspen Plus and other software’s. FO desalination process unit is created in Aspen Plus and the model is develops in Microsoft Excel. A validation of FO desalination is done by running the FO desalination simulation at the same condition with the experimental and the result of FO desalination is compared.